EFFICIENCY OF ENSURING VETERINARY WELFARE ON INFECTIOUS DISEASES OF LARGE AND SMALL HORSE CATTLE IN BAYSERKE-AGRO LLP - Dosmukhambetov T.M.; Sultanov A. A.; Ivanov N. P.; Namet A.M.; Sadykulov T. S.; Bekenov D. M. (Scientific Journal of Pedagogy and Economics, 2019)
The article provides the epizootological characteristics of livestock farms of Bayserke-Agro LLP and the adjacent territories. In the Almaty region in the territory adjacent to the farms of Bayserke-Agro LLP, we studied the epizootic situation of especially dangerous animal diseases. At the same time, cases of detection of pathogens of tuberculosis, brucellosis, listeriosis, viral diarrhea, salmonellosis, moraxellosis, necrobacteriosis and others were reported.